Determination of The Shortest Route Based on BFS Algorithm for Purpose to Disaster Evacuation Shelter - Sularno, Sularno; Mulya, Dio Prima; Astri, Renitra; mulya, Dwiki (Scientific Journal of Informatics, 2021)
Purpose: This study aims to determine the shortest route that can be taken by the user (community) during a disaster to reduce the risk of a greater number of victims by using the Breadth-first search algorithm, which is integrated into a web-based GIS application. By determining the starting point, which is the user's position when the disaster occurs, and then determining the endpoint, which is the location of the closest shelter, it will be possible to calculate the shortest distance that can be reached by the user at that time. Methods: The method chosen in this study is a waterfall because each step of the research carried out must be sequential and structured to avoid the risk of errors in each sequence of processes carried out. Result: The results of this study can be proven by doing manual calculations to determine the shortest distance, which will later be compared with the results of applications that have been designed using the BFS algorithm. Novelty: The novelty of this research is the development of GIS as a disaster mitigation education. The function of this research can help the community in finding an evacuation route in the event of a tsunami disaster.